ANALISIS AKTIVITAS SESAR AKTIF BARIBIS DAN RISIKO KEGEMPAAN DKI JAKARTA DENGAN PENDEKATAN DETERMINISTIK DAN PROBABILISTIK - Ruben
The special capital region of Jakarta and its surroundings are an area with a relatively complex geological structure due to the subduction of the Australian plate beneath the Eurasian plate. This tectonic activity resulted in the formation of three active faults in this area, including the Cimandiri, Lembang, and Baribis faults. These three faults are located close to areas with high population densities. This study aims to obtain evidence of the Baribis Fault activity through observing and determining the hypocenter of recorded microearthquakes in this region; to obtain an overview of disaster risk due to the Baribis Fault seismic activity, so it may become the main reference and information for estimating potential economic losses due to earthquake in DKI Jakarta. The microearthquake monitoring process was carried out by installing 7 (seven) units of borehole seismometer for the period July 2019 to Agustus 2020 at a location identified as the existence of the Baribis fault leading to Jakarta, then in 2020 the seven borehole seismometers were moved to the east of Jakarta, to the area around Karawang and Purwakarta. Hypocenters were determined using the Geiger method with Hypoellipse software. Based on the results of monitoring the incidence of microearthquakes and determining the hypocenter during the past year, there were 187 microearthquakes with the general location on the mainland and south of West Java, where there were records of the earthquake with the epicenter position not far from the network location or the position of Baribis fault. Based on the location distribution, the earthquakes were divided into 4 clusters, namely cluster 1 that was located on the west side of Mount Salak, cluster 2 that was located on the north side of Mount Gede, cluster 3 that was located on the south of Purwakarta or the north of the Cimandiri fault, and cluster 4 that was located on the fault Baribis. Generally, the earthquakes that occurred in Jakarta and its surroundings are located in the south of West Java, however, the earthquakes recorded in this study become evidence that the Baribis fault towards Jakarta is classified as active. The results of microearthquake observations provide better information the parameters of the Baribis fault. It can be used as input data in the seismic risk analysis process with a probability approach using the eventbased method and a deterministic approach based on earthquake scenarios in the DKI Jakarta area. Computation of earthquake scenarios from the Baribis fault source produces high earthquake intensity in Jakarta, Bogor and Serang. Based on historical data records and deterministic scenarios, it is indicated that Jakarta has experienced damage due to earthquakes from the active Baribis fault. The earthquake hazard probability approach is represented by the peak ground acceleration and the response spectrum at a possible period of 2% and 10%probability of exceedance in 50 years, considering local conditions based on the average shear wave velocity to a depth of 30 m (????!"#). The earthquake hazard contour map produces trends in the value of the concentration of ground motion in areas close to the earthquake source zone and on soft rock types, especially in DKI Jakarta. Based on the earthquake potential, residential data, geological conditions, and vulnerability curves, an earthquake risk model due to the Baribis fault could be described.